(untitled) (International Journal of Engineering and Computer Science, 2016)
Ration distribution is one of the big issues that involves corruption and smuggling of goods. The only reason of this to happen is because every work in the ration shop involves manual work. These irregularities activities are happen like – the entries which are incorrect in collection record of store containing wrong stock information of the products that is supplied to the peoples, at times it may chance of distribution of minimum quality products than the actual products given by the Government for providing to the public, also the information regarding the available stock quantity in a ration shop that is supplying by the Government to the public. In this paper we propose the concept of changing manual work in public distribution system by automated system which can be installed at the ration shop with ease. This would bring the transparency in rationing system as there will be a direct communication between user and Government through this system.